Ferdinand Verbiest and his Chinese books according to his correspondence (The Macau Ricci Institute Journal, 2023)
In view of Verbiest’s central position in Jesuit contacts with Chinese authorities andcalendar specialists in the period 1660-1688, it is worth collecting the few precise titlereferences he gives in his letter corpus, which was recently extended and revised (132 items) to include the Chinese works and authors he was acquainted with and which he apparently used. Their number is rather low, and the titles are stemming from expected libraries and collections, and are for obvious reasons mostly found in letters to his European colleagues in China, as European readers were unacquainted with Chinese. But even this low number - which certainly covers only a small part of the real number of books he used - contains some revealing titles; at any rate, it suggests a various, composite reading, and in addition it reflects some unexpected, and rather surprising assessments, with regard to the (absence of) logical structure and of (technical) illustrations.